INFLUENCE OF STRIATED MUSCLE ACTIVITY ON THE LETHAL DOSE OF K STROPHANTHOSIDE - POZO, EFREN C DEL; PARDO; ANGUIANO (INSTITUTO DE SALUBRIDAD Y MEDICINA TROPICAL, CD. MEXICO, DF, MEX, 1977)
The lethal dose of k-strophanthoside was determined in 40 cats subjected to muscular work by the continuous stimulation of both sciatic nerves. The average lethal dose for these animals was significantly greater than that determined under identical condit
J PHARMACOL EXP THER
Keywords: INFLUENCE, STRIATED, MUSCLE, LETHAL, DOSE, STROPHANTHOSIDE; CIENCIAS MEDICAS; FARMACOLOGIA; FARMACOLOGIA EXPERIMENTAL